Differential proinflammatory responses of colon epithelial cells to SARS-CoV-2 spike protein and Pseudomonas aeruginosa lipopolysaccharide - Yılmaz Aysegul; Turk Seyhan; Malkan Ümit Yavuz; Haznedaroglu İbrahim Celalettin; Ucar Gulberk; Ozguven Sukru Volkan; Turk Can (Türk Biyokimya Dergisi)
The study aims to compare the proinflammatory responses of colon epithelial cells to two potent virulence factors: lipopolysaccharide (LPS) from Pseudomonas aeruginosa and spike (S) protein of SARS-CoV-2. Both agents are known to induce significant inflammatory responses, leading to severe clinical manifestations.